Heyran Form in Kurdish Music: in the Context of Style and Performance - Khakmand Majeed Abdullah; Nahro Zagros (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This is a qualitative research based on fieldwork on heyran form in Kurdish music in and around the vicinity of Erbil city. attempts to analyze heyran in its unique musical form. Several oral testaments have been gathered for this research, which they offer some exceptional insights to heyran form. Also, a number for heyran examples have been studied and notated for better understanding. This research will be a good source for not only those who study heyran, but also those who are interested to examine the other musical forms in Kurdish musical culture by using the very method on which this research is based.